Cognitive outcome of 458 children over 25 years of neonatal screening for congenital hypothyroidism - Julita Maria Pelaez; Juliana Cristina Romero Rojas-Ramos; Mouseline Torquato Domingos; Marcella Rabassi de Lima; Gabriela de Carvalho Kraemer; Adriane de Andre Cardoso-Demartini; Rosana Marques Pereira; Luiz de Lacerda; Suzana Nesi-França (Elsevier, 2023)
Objectives: To describe the neurocognitive profile of 458 children with congenital hypothyroidism detected by neonatal screening, followed under the same treatment protocol over 25 years. To correlate estimated full-scale IQ (FSIQ) scores with age at the start of treatment, disease severity, and maternal education. Methods: Observational, analytical, retrospective, and longitudinal cohort study, that evaluated children detected between 1991 and 2014, who underwent at least one psychometric assessment (WPPSI- R and/or WISC-III). Estimated FSIQ scores are described and correlated with prognosis determinants. Results: Median T4 at diagnosis was 2.8 μg/dL (0.0-16.5), the median age at the start of treatment was 18.5 days (3-309). Maternal education (n = 445): 2.7% of illiteracy, 59.8% with basic education. Estimated FSIQ scores were 88.0 (±11.8) in WPPSI-R (age 5.6 ± 0.5 years) and 84.1 (±13.0) in WISC-III (age 9.1 ± 1.4 years). The intellectual deficit was identified in 11.6%. Correlation between age at the start of treatment and estimated FSIQ was found only in the WPPSI-R test (p = 0.02). Initial T4 and maternal education significantly correlated with estimated FSIQ scores in both tests, with the latter being the most important determining factor. Conclusions: In this large cohort of mainly low socioeconomic status children, most children achieved normal cognitive levels; however, a significant percentage presented with below-average estimated FSIQ scores and intellectual deficits. Maternal education was the main determining factor in cognitive level followed by hypothyroidism severity.